eCM 2017
DOI: 10.22203/ecm.v033a16
|View full text |Cite
|
Sign up to set email alerts
|

Local induction of inflammation affects bone formation

Abstract: To explore the influence of inflammatory processes on bone formation, we applied a new in vivo screening model. Confined biological pockets were first created in rabbits as a response to implanted bone cement discs. These biomembrane pockets were subsequently used to study the effects of inflammatory stimuli on ectopic bone formation within biphasic calcium phosphate (BCP) constructs loaded with TNF-α, lipopolysaccharide (LPS) or lipoteichoic acid (LTA), all with or without bone morphogenetic protein (BMP)-2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…This dose is far less than the LD50 (3 mg/kg) [36]. Previous studies utilized 345 to 17,253 times more LPS compared to our doses in vivo [17,18,46], which apparently hampered bone formation [18,46]. As with these studies, in our study, although LR-G rereleased LPS immediately, bone formation was still delayed for 1 week, which might due to the temporal burst effect (inducing high dose of LPS).…”
Section: Discussionmentioning
confidence: 46%
“…This dose is far less than the LD50 (3 mg/kg) [36]. Previous studies utilized 345 to 17,253 times more LPS compared to our doses in vivo [17,18,46], which apparently hampered bone formation [18,46]. As with these studies, in our study, although LR-G rereleased LPS immediately, bone formation was still delayed for 1 week, which might due to the temporal burst effect (inducing high dose of LPS).…”
Section: Discussionmentioning
confidence: 46%
“…Only under mild inflammatory conditions may pro‐inflammatory cytokines or bacteria‐derived antigens promote osteoblast differentiation in resident bone‐lining or recruited osteoprogenitor cells. In line with this hypothesis, it has been shown that a transient inflammatory reaction to a low‐dose of bacterial stimuli promotes periosteal or ectopic bone formation, but that the sustained inflammation caused by a high‐dose of bacterial stimuli leads to predominantly osteolysis or impaired ectopic bone formation …”
Section: Discussionmentioning
confidence: 85%
“…95 To illustrate, the proinflammatory cytokines TNF-α and interleukin (IL)-17 are upregulated during bacterial infection, 22 and their transient expression is known to have pro-osteogenic effects on osteoprogenitor cells. 50,100,102,103 On the other hand, increased cell death, comprised vascularization, and uncontrolled osteoclast activity will be most profound in the vicinity of the bacterial burden. 1,7,14,15,17 Moreover, the increased influx of immune cells can lead to the production of soluble factors hampering osteogenesis.…”
Section: What Is the Mechanism Of The Observed Pro-osteogenic Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…[324][325][326] From a different perspective, there is evidence to support that the heightened inflammatory response resulting from immune training could exacerbate biomaterial-related inflammation and fibrosis, whereas LPS could act prophylactically to inflammatory fibrosis. [325] In the same line of reasoning, PRR ligands can differently impact the osteogenic response, [327][328][329][330][331] and it should be elucidated whether proosteogenic adjuvants also render implants with anti-infective properties. As a potential caveat, the innate immune training concept takes its advantage form the metabolic programming of host cells.…”
Section: Adjuvants For Innate Immunity Trainingmentioning
confidence: 99%